Role of contextual and compositional characteristics of schools for health inequalities in childhood and adolescence: A scoping review - Herke, Max; Moor, Irene; Winter, Kristina; Hack, Miriam; Hoffmann, Stephanie; Spallek, Jacob; Hilger-Kolb, Jennifer; Herr, Raphael M.; Pischke, Claudia; Dragano, Nico; Novelli, Anna; Richter, Matthias (BMJ Open, 2022)
Objectives To synthesise the evidence on the role of compositional or contextual characteristics of schools in the association between students' socioeconomic position and their health in primary and secondary education in developed economies. Design Scoping review. We included studies examining the role of at least one school or class characteristic on students' health inequalities and was published since 1 January 2000, in English or German. We searched PubMed/Medline, Web of Science and Education Resources Information Center. We provided a narrative synthesis and an overview of findings. School characteristics were grouped into five broad categories: school composition, school climate, school policies and organisation, food environment and facilities. Results Of 8520 records identified, 26 studies were included. Twelve studies found a moderating and 3 a mediating effect. The strongest evidence came from studies examining the moderating effect of school composition, that is, the negative impact of a low individual socioeconomic position on mental health and well-being was aggravated by a low average socioeconomic position of schools. Evidence concerning the role of school climate, school stratification (eg, performance base tracking) and sponsorship, food environment and sport facilities and equipment was generally weak or very weak and mostly based on singular findings. Overall, favourable meso-level characteristics mitigated the negative impact of low individual socioeconomic position on health outcomes. Conclusions School characteristics affect health inequalities in children and adolescents to some degree, but future research is necessary to strengthen the existing evidence and address under-represented aspects in school characteristics and health outcomes.
CRIS-Team Scopus Importer:2022-11-28
Keywords: community child health; health policy; public health